The value of LAM and LprG in extracellular vesicles in the diagnostic and therapeutic field of renal tuberculosis - Peng, Xuefeng; Li, Yue; Jin, Suiyang; Wang, Qiang (Frontiers in Tuberculosis, 2025)
Extracellular vesicles have been a hot research topic in recent years, and the diagnostic and therapeutic value of LprG and LAM, two key markers present in extracellular vesicles secreted by Mycobacterium tuberculosis or Mycobacterium tuberculosis-infected immune cells, in tuberculosis, has been widely emphasized in recent years. Genitourinary tuberculosis is a common form of extrapulmonary tuberculosis, and renal tuberculosis accounts for more than 20% of patients with Genitourinary tuberculosis. In this paper, we summarize the findings and research ideas of LprG and LAM in the diagnosis and treatment of renal tuberculosis in recent years and conclude that LprG and LAM have their unique diagnostic value in the intrapulmonary and extrapulmonary fields and can be used as a new potential idea for vaccine or immunotherapy in the future for research.